Synthesis of (Poly-methyl Methacrylate-lead Oxide) Nanocomposites and Studying their A.C Electrical Properties for Piezoelectric Applications - Dalal Hassan; Ahmed Hashim (Institute of Advanced Engineering and Science, 2018)
Piezoelectric materials have been prepared from (poly-methyl methacrylate-lead oxide) nanocomposites for electronic applications. The lead oxide nanoparticles were added to poly-methyl methacrylate by different concentrations are (4, 8, and 12) wt%. The structural and dielectric properties of nanocomposites were studied. The results showed that the dielectric constant and dielectric loss of nanocomposites decrease with increase in frequency of applied electric field. The A.C electrical conductivity increases with increase in frequency. The dielectric constant, dielectric loss and A.C electrical conductivity of poly-methyl methacrylate increase with increase in lead oxide nanoparticles concentrations. The results of pressure sensor showed that the electrical resistance of (PMMA-PbO2) nanocomposites decreases with increase in pressure.